Development of the Instructional Model to Enhance Learning Happiness of Junior High School Students - Prakobvorakan, Bunyakon; Naowanondha, Adisorn; Tanya, Somboon (Ratchaphruek Journal, 2023)
The research objectives were to: 1) study the components and indicators of learning happiness and instructional guidelines; 2) develop an instructional model; and 3) find out the effect of using the model to enhance learning happiness. The sample consisted of fifteen grade 7 students at Ban Ngew school by multi-stage random sampling. The data tools were the teaching observation form, the learning happiness scale, the learning achievement scale, and the satisfaction questionnaire. The statistics used were mean ( ), standard deviation (S.D.), and t-test. The study revealed that 1) the two components and indicators of learning happiness were learners and friends, and there were 3 aspects of the instructional mode, which were teachers, environment, and measurement and evaluation, 2) the model contained five components: principles, objectives, learning management, measurement and evaluation, and successful conditions. The results of the investigation revealed that the model was appropriate at a high level, and 3) the results of the model testing showed that after using the model the students' learning happiness, and learning achievement were significantly higher than before at the .05 level, and the overall satisfaction of the students was at a high level.